2014
DOI: 10.1073/pnas.1402342111
|View full text |Cite
|
Sign up to set email alerts
|

Dietary history contributes to enterotype-like clustering and functional metagenomic content in the intestinal microbiome of wild mice

Abstract: Understanding the origins of gut microbial community structure is critical for the identification and interpretation of potential fitnessrelated traits for the host. The presence of community clusters characterized by differences in the abundance of signature taxa, referred to as enterotypes, is a debated concept first reported in humans and later extended to other mammalian hosts. In this study, we provide a thorough assessment of their existence in wild house mice using a panel of evaluation criteria. We ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
159
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(174 citation statements)
references
References 31 publications
14
159
0
1
Order By: Relevance
“…that could not identify a significant effect of environmental contamination or habitat type on cecal diversity (40). They also support recent studies of wild European M. musculus populations that observed that large geographical distances were the most significant factor in explaining microbiota variation and that host genetics and diet had relatively minor effects on variation (41,42). Other natural experiments investigating the structure of the microbiota in insects (13,14), primates (15)(16)(17), and bats (18) also support our results.…”
Section: Figsupporting
confidence: 90%
“…that could not identify a significant effect of environmental contamination or habitat type on cecal diversity (40). They also support recent studies of wild European M. musculus populations that observed that large geographical distances were the most significant factor in explaining microbiota variation and that host genetics and diet had relatively minor effects on variation (41,42). Other natural experiments investigating the structure of the microbiota in insects (13,14), primates (15)(16)(17), and bats (18) also support our results.…”
Section: Figsupporting
confidence: 90%
“…Laboratory mice were housed in conventional or specific pathogen-free facilities at the WZW School of Life Sciences (TU München), the Institute for Medical Microbiology and Hygiene (Universitätsklinikum Freiburg) or the Rodent Center (ETH Zurich). Samples from mice captured in the wild were obtained as described previously 42 . Starting materials for bacteria isolation included fresh faeces collected from living mice, mucosal samples, as well as small intestinal, caecal or colonic content collected from mice that had been euthanized by CO 2 inhalation or neck dislocation.…”
Section: Methodsmentioning
confidence: 99%
“…The existence of discrete structures for gut microbiota has not been convincingly demonstrated (30) and represents a crucial assumption in applying an appropriate prediction model. Nonetheless, we used the original tutorial to define enterotypes (http://enterotype .embl.de/enterotypes.html) in the present study, because it has been demonstrated to be useful to correlate the gut microbial community structure with host biomarkers and diet (31,32). In our study, enterotyping clustered the microbiota taxonomic structures of the fecal samples in two groups corresponding to the most common enterotypes of healthy adult populations, namely, the Bacteroides-dominant (Ba) and the Prevotella-dominant (Pr) enterotypes (22,33).…”
Section: Discussionmentioning
confidence: 99%